Identifikasi Parameter KualitasAir untuk Kepentingan Marikultur di Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara - Mudeng, Joppy D; Ngangi, Edwin L.A; Rompas, Robert J (e-Journal BUDIDAYA PERAIRAN, 2015)
The aimed of research was to identify and analyze the natural resources potential for mariculture development in Regency of Sangihe Archipelago. This research was carried out at Talengen waters in Central  Tabukan District and Manalu waters in South Tabukan District.  Research method was survey and the data was analyzed descriptively.   Primary data to be collected included water quality and socio economic data.  The second was obtained through interview to respondent chosen randomly.  Questionnaire was also used in collecting data.  Research result  showed that water quality at Talengen and Manalu waters was optimal and thus feasible for mariculture. However,  the development of mariculture at these locations should consider other utilization whether for fishery, ecotourism and conservation. Keywords:  mariculture, water quality, Talengen Waters, Manalu Waters